Rāwī Ḍa’īf in Kitab Ṣaḥīh; Analysis Toward Muḥammad Bin ‘Abd Al-Raḥmān Al-Ṭufāwī and His Narration in Ṣaḥīh Al-Bukhārī - Rizal Samsul Mutaqin; Tibaus Surur Tibaus (Al-Bukhari, 2021)
Hadith has its classification. Hadith consists of ṣahih and ḍa'īf. The s}ahīh is accepted in his hadith while the ḍa'if is rejected in his hadith. But not every hadith ḍa'īf is rejected. There are several criteria of hadith ḍa'īf that can be accepted, namely ḍa'īf which level of ḍa'īf is not to severe. The scholars have compiled the book of hadith from the category of s}ahīh until there is a ḍa'īf. The most ṣahih books are found in the books of ṣahih Al-Bukhārī and Muslim and the rest, like the sunan al-'Arba'ah where the hadiths in which ṣahih are also ḍa'īf. The purpose of this study is to know the position of Muḥammad bin 'Abdirraḥmān aṭ-Ṭufāwī in the view of the scholars of jarh wa ta'dīl and to know the position of the hadiths narrated by aṭ-Ṭufāwī in Ṣaḥīḥ Al-Bukhārī. The methodology used in this research is descriptive analysis, which consists of three stages of research, namely the stages of orientation, exploration and analysis. It does not matter if there is a hadith ḍa'īf out of those two books of ṣahih Al-Bukhārī and Muslim. However, it would be a question if there is an indication of the hadith ḍa'if written in those s}ahīh books. Whereas in the authenticity of the hadith in it has been tested, the scholars have acknowledged the authenticity of the hadith in the book. But here the author found the narrator which indicated as a ḍa'īf in the book ṣahih Al-Bukhārī, the narrator is Muḥammad bin 'Abd al-Raḥman al-Ṭufāwī. The evaluation of jarh against him is found in many ways, among them it is evaluated as tadlis, he likes to narrate munkar hadith and tasyayyu '. Thus, this study was conducted to find out fully and thoroughly how the scholars view him. And what is the position of those hadiths narrated by Muḥammad bin ‘Abdirraḥmān aṭ-Ṭufāwī in Ṣaḥīḥ Al-Bukhārī.